COLLECTIVE ECONOMIC EMPOWERMENT THROUGH RELIGIOUS MODERATION AND THE VALUES OF DALIHAN NATOLU IN BATANGTORU DISTRICT - Abdul Nasser Hasibuan; Windari; Sulaiman Efendi; Ahmad Fahruzi Harahap (RADJA PUBLIKA, 2025)
This community service program addresses the need for strengthening religious moderation and social cohesion in Batangtoru District, North Sumatra, a region characterized by diverse religious, cultural, and ethnic backgrounds. Despite this diversity, limited understanding of religious moderation and minimal cross-belief interaction have posed social challenges. The program aims to enhance cooperative (gotong royong) economic empowerment and cross-identity social cohesion by internalizing the local cultural values of Dalihan Natolu within four community business groups. Using a community-based empowerment approach and the Participatory Action Research (PAR) method, the program integrates religious moderation principles and local wisdom to foster social solidarity, mutual trust, and economic collaboration. Collective economic practices including joint farming, micro-enterprises, and clan-based cooperatives—serve as practical platforms for applying these values. The results demonstrate significant positive outcomes across three dimensions. Economically, group incomes increased by 15–20%, production efficiency improved through collective procurement, and marketing capacities strengthened. Socially, intergroup trust, open communication, deliberative decision-making, and conflict resolution through customary dialogue (martonggo raso) were enhanced. Culturally, Dalihan Natolu values were reflected in equitable task distribution, respect for individual capacities, and intergenerational solidarity. Overall, the program confirms that local cultural approaches can effectively support economic empowerment, strengthen social capital, and promote sustainable religious moderation, making it suitable for replication in other culturally diverse regions.